2000
DOI: 10.1046/j.1469-0705.2000.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness and histological abnormalities in women on hormonal replacement therapy: a transvaginal ultrasound/hysteroscopic study

Abstract: Endometrial thickness in patients on sequential HRT, measured soon after withdrawal bleeding, is not significantly different from thickness measured in patients on combined HRT. Patients on HRT with an endometrial thickness of > 4 mm could be considered for histological sampling. The prevalence of abnormal endometrial findings in patients with a thick endometrium is significantly higher than the prevalence observed in patients with unexpected bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…In women on sequential combined therapy, the false-positive rate might be reduced by measuring the endometrial thickness within a week after the last progestin pill. This is supported by the findings of Omodei et al, who showed that endometrial thickness did not differ in women on sequential or continuous combined HRT (3.6 mm vs. 3.2 mm) if the measurement in question were taken on about the fifth day following the last progestin pill (15).…”
Section: Discussionsupporting
confidence: 74%
“…In women on sequential combined therapy, the false-positive rate might be reduced by measuring the endometrial thickness within a week after the last progestin pill. This is supported by the findings of Omodei et al, who showed that endometrial thickness did not differ in women on sequential or continuous combined HRT (3.6 mm vs. 3.2 mm) if the measurement in question were taken on about the fifth day following the last progestin pill (15).…”
Section: Discussionsupporting
confidence: 74%
“…Endometrial thickness did not differ in women on sequential or continuous combined HRT (3.6 mm versus 3.2 mm) if measured at about the fifth day after taking the last progestogen pill …”
Section: Investigationmentioning
confidence: 85%
“…Among women with postmenopausal bleeding, a thin endometrium (<5 mm) safely excludes endometrial pathology and may not require any further investigation unless recurrent/persistent bleeding or any high‐risk factors are present …”
Section: Investigationmentioning
confidence: 99%
“…No difference in the incidence of endometrial cancer was identified between the two groups, however it concluded that women with unscheduled bleeding on HRT require further investigation by hysteroscopy and biopsy if the endometrial thickness was greater than 8 mm . Comparing combined HRT to sequential HRT, the likelihood of identifying an endometrial pathology was significantly higher in patients with endometrial thickness >4 mm than the incidence observed in patients with unscheduled bleeding …”
Section: Endometrial Hyperplasiamentioning
confidence: 86%